2014
DOI: 10.1113/jphysiol.2013.262998
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Rac1 is required for smooth muscle contraction

Abstract: Key pointsr The role of the small G-protein Rac1 was investigated in smooth muscle, using a smooth muscle-specific knockout mouse and pharmacological blockers. r The results demonstrate a novel Rac1-associated signalling pathway for regulation of smooth muscle contraction. AbstractThe role of the small GTP-binding protein Rac1 in smooth muscle contraction was examined using small molecule inhibitors (EHT1864, NSC23766) and a novel smooth muscle-specific, conditional, Rac1 knockout mouse strain. EHT1864, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…Data from our current studies have provided evidence to suggest that Rac1 activation is upstream to CD36 expression since EHT1864, a known inhibitor of Rac1 [31, 32], attenuated HG-induced CD36 expression in INS-1 832/13 cells. Our findings are also compatible with recent observations of Elumalai and associates demonstrating regulatory roles for Rac1-Nox2 signaling axis promotes CD36 expression in INS-1 cells under the duress of glucotoxic conditions [19].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Data from our current studies have provided evidence to suggest that Rac1 activation is upstream to CD36 expression since EHT1864, a known inhibitor of Rac1 [31, 32], attenuated HG-induced CD36 expression in INS-1 832/13 cells. Our findings are also compatible with recent observations of Elumalai and associates demonstrating regulatory roles for Rac1-Nox2 signaling axis promotes CD36 expression in INS-1 cells under the duress of glucotoxic conditions [19].…”
Section: Discussionmentioning
confidence: 79%
“…However, there was a 50% reduction in nuclear association of N17 mutant in cells under the same conditions [Figure 2; Panels A and B]. In the second approach, we utilized EHT1864, a known inhibitor of Rac1 [31, 32] to functionally inactivate endogenous Rac1 and then assessed nuclear association of Rac1 under LG and HG conditions. Data in Figure 2 [Panels C and D] demonstrate decreased localization of Rac1 in INS-1 832/13 cells exposed to EHT1864.…”
Section: Resultsmentioning
confidence: 99%
“…While this study was under preparation, Rahman et al (Rahman et al, ) reported quite recently that EHT1864 significantly inhibited both phenylephrine and high K + induced contraction of mouse saphenous artery, while NSC23766 inhibited phenylephrine but not high K + induced contraction. High concentration (100 μM) of NSC23766 completely inhibited phenylephrine induced increase in cytosolic Ca 2+ and contraction of saphenous artery, although it did not inhibit high K + induced contraction.…”
Section: Discussionmentioning
confidence: 86%
“…12 Recently, Rac inhibitors (EHT1864, NSC23766) have been described to either potentiate or inhibit smooth muscle contraction depending on the vasoconstrictor used. 13 Rho GTPases and vascular NO signaling Endothelial cells are key regulators of the arterial tone by releasing vasoactive factors that modulate the contractile state of the underlying smooth muscle cells, in a great part through the regulation RhoA activity. While endothelium-derived contracting factors such as Et-1 activates RhoA, NO, the most important physiological endothelial relaxing factor, inactivates RhoA/Rock pathway.…”
Section: Role Of Rac1 In Vascular Smooth Muscle Contractionmentioning
confidence: 99%